Evaluation of buffaloes' follicular dynamics and stress state under different ovulation synchronization protocols - Stella, Edmilson Daniel [UNESP]; Ramos, Alcides de Amorim [UNESP]; de Ruediger, Felipe Rydygier [UNESP]; Dantas, Ariane [UNESP]; Yamada, Paulo Henrique [UNESP]; Codognoto, Viviane Maria [UNESP]; Salgado, Letícia Cristina [UNESP]; Brochine, Suzane [UNESP]; Oba, Eunice [UNESP] (Colegio Brasileiro de Reproducao Animal - CBRA, 2018)
The aims of the present study were to analyze the effect of different hormonal protocols using an implant containing Norgestomet, at the ovulation synchronization in buffaloes and to verify the effect of the stress caused by manipulation of the herd during the experiment. Twenty-four female Murrah breed buffaloes, lactating, multiparous, aged from three to eight years, with a body condition score of 3.5 or higher (0 to 5) and with more than 45 days post partum, were used. These females were randomly distributed into one of the three groups (group 1, group 2 and group 3) with eight subjects in each. On day 0 (day 0), all animals received an ear progesterone implant with 3.0 mg of Norgestomet and an intramuscular (IM) injection with 2.0 mg of estradiol benzoate (EB). The implants were removed after nine days (day 9) and one single dose of PGF2α (0.15 mg d-cloprostenol, IM) was administered to all animals. On the same day, the group'1 and group 3 buffaloes were treated with 500 UI of eCG (IM). Two days later (day 11), 1000UI of hCG (IM) were administered to the group 1 and group 2 buffaloes. After the implant had been removed, an ultrasound evaluation was performed every 12 h, in order to access the ovarian follicular dynamics, using an Aloka 500 equipment with a 5 MHz transrectal probe. Blood samples were also taken on days 0, 9 and 11 to determine the plasmatic concentrations of cortisol and progesterone. No difference was observed in the ovulation rate (group 1: 62.5%, group 2: 50%, group 3: 75%). However, the size of the preovulatory follicles and the plasmatic concentration of cortisol had (P < 0.05). G3 was the most efficient group in promoting the ovulation synchronization, which suggests that this protocol can be used in Fixed Timed Artificial Insemination programs (FTAI) among postpartum, lactating Murrah breed buffaloes'.
Keywords: Cortisol; ECG; FTAI; HCG; Progesterone